Plain X-ray can be a Good Tool for the Diagnosis of Horse Shoe Kidney (Journal of Bangladesh College of Physicians and Surgeons, 2012)
Not available   DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11369   J Bangladesh Coll Phys Surg 2012; 30: 56-57